Implications of Isoprostanes and Matrix Metalloproteinase-7 Having Potential Role in the Development of Colorectal Cancer in Males - Rasool, Mahmood; Malik, Arif; Ghuman, Ahmad Ashar; Ashraf, Muhammad Abdul Basit; Arooj, Mahwish; Waquar, Sulayman; Zahid, Sara; Shaheen, Sumera; Qazi, Aamer; Naseer, Muhammad Imran; Zamzami, Mazin A.; Al-Ghafari, Ayat; et al. (Frontiers in Oncology, 2018)
ABSTRACT Background: Colorectal cancer is the third most common type of cancer and leading cause of death worldwide. Major risk factors involved in the development of colorectal cancer are increased dietary sources, genetics and increasing age. Purpose of study was to find the role of different variables in the progression of colorectal cancer. Methodology: 50 blood samples from colorectal cancer patients and 20 samples from control were collected. Serum was separated from the blood by centrifugation. This serum was assessed for several anti-oxidants like superoxide dismutase, glutathione, glutathione peroxidase, glutathione reductase, catalase, vitamin A, C and E, and pro-oxidants such as malondialdehyde, AOPPs and AGEs according to their respective protocols. MMP-7 and isoprostanes were assessed by ELISA kits. Results: Lower levels of GSH (4.86±0.78 Vs 9.65±1.13 µg/dl), SOD (0.08±0.012 Vs 0.46±0.017 µg/dl), CAT (2.45±0.03 Vs 4.22±0.19 µmol/mol of protein) and GRx (5.16±0.06 Vs 7.23±0.36 μmol/ml) in the diseased group were recorded as compared to control. Higher levels of GPx (6.64±0.19 mmol/dl) were observed in the subjects in comparison to control group (1.58±0.30 mmol/dl). Highly significant decreased levels of vitamin A (0.81±0.07 Vs 2.37±0.15 mg/ml), E (15.42±1.26 Vs 25.96±2.19 mg/ml) and C (47.67±7.69 Vs 80.37±10.21 mg/ml) were observed in the patients in contrast to control group.The reversal of anti-oxidants in later stages of CRC may be due to compensatory mechanisms in cancerous cells. The levels of MDA (nmol/ml) were also assessed which shows significantly increased level in colorectal cancer patients as compared to control groups (3.67±0.19 Vs 1.31±0.27). The levels of protein oxidation products [AGEs (2.74±0.16 Vs 0.84±0.05 IU) and AOPPs (1.32±0.02 Vs 0.82±0.07 ng/ml)] were significantly increased in subjects as compared to control. The levels of MMP-7 (64.75±3.03 Vs 50.61±4.09 ng/ml) and isoprostanes (0.71±0.03 Vs 0.16±0.02 ng/ml) were also analyzed. This shows that the levels of isoprostanes increased due to high lipid peroxidation mediate higher levels of MMP-7 which promotes development of colorectal cancer. Conclusion: Following study suggested that elevated oxidative and inflammatory status along with lipid peroxidation and matrix metalloproteinases are the chief contributors in the progression of colorectal cancer.